2020
DOI: 10.1016/j.cegh.2020.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of variations in morphology and attachment of frenum in diverse population - A cross-sectional study

Abstract: Background: Frenal attachments are thin folds of mucous membrane with enclosed muscle fibers that attach the lips to the alveolar mucosa and underlying periosteum. It also has septomaxillary ligament that transmits septal growth force to premaxilla. Most often, during the oral examination of the patient the dentist gives very little importance to the frenum, for assessing its morpholology and attachment. However, it has been seen that an abnormal frenum can be an indicator of a syndrome or can cause severe muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…These studies have related their findings based on age, gender, race, and ethnicity. 10,14,15,[18][19][20] Inconsistent to our study, mucosal frenal attachment was to be prevalent in studies done by Kotian et al, 18 Pandian et al 21 We also observed similar findings based on Mirko's classification of maxillary labial frenum according to location.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These studies have related their findings based on age, gender, race, and ethnicity. 10,14,15,[18][19][20] Inconsistent to our study, mucosal frenal attachment was to be prevalent in studies done by Kotian et al, 18 Pandian et al 21 We also observed similar findings based on Mirko's classification of maxillary labial frenum according to location.…”
Section: Discussionsupporting
confidence: 86%
“…1,24,25 In this instance, the papillary and papillary penetrating frenum attachment are the only two considered as pathological. 15 In this study, very less number of the papillary type (6.2%) and papillary penetrating type (4.1%)…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…This finding agrees with Lertpimonchai et al, 2017;Divater et al, 2019 and can be justified by interference with oral hygiene measures, and the accumulation and retention of plaque. Besides, the opened periodontal pocket, made it easier for food particles to enter (Rathod et al, 2020) In terms of the association between oral hygiene and gingivitis, patients with poor oral hygiene had severe and moderate gingivitis, while those with satisfactory oral hygiene showed mild, moderate, and no gingivitis. These results were in agreement with Pawlaczyk-Kamieńska, Torlińska-Walkowiak and Borysewicz-Lewicka, 2018 and can be linked to the amount of bacterial plaque accumulated on the tooth surface which initiates the inflammatory process in the gingiva that increases the likelihood of gingivitis (Pawlaczyk-Kamieńska, Torlińska-Walkowiak and Borysewicz-Lewicka, 2018).…”
Section: Discussionmentioning
confidence: 99%